Edge slip zone size of misaligned common edge contacts - Clark, Z; Ramesh, R; Hills, D (Sage Publications, 2017)
We investigate the effect of a slight misalignment on the behaviour of common edge contacts, developing a procedure for estimating the extent of slip at the edge. Better estimations, compared to one inferred from Williams’ solution, are found by introducing the effects of slip and further geometry. The refined asymptote is compared with the exact answer for an example problem.